Pemaknaan Pesan Konten TikTok Tentang Self Harm dan Implikasinya Bagi Generasi Z - Vania Falah Nabila Putri; Yunita Indinabila; E. Rizky Wulandari; Eddy Christijanto; Supriadi (LPPM Stikosa - AWS, 2026)
The interpretation of messages in TikTok content themed around self-harm among Generation Z is important because this platform is increasingly used as a place to express emotions. As a generation familiar with digital culture, Gen Z understands messages not only from direct narratives but also from the symbols, music, and visuals used in the content. This study uses a qualitative approach with a phenomenological method through in-depth interviews with five informants aged 18 to 24 who are active on TikTok. Data analysis is carried out through the process of reduction, presentation, and conclusion drawing, as well as connecting the findings with New Media Theory, Social Cognitive Theory, and Berlo's Communication Model (SMCR). The research results show that self-harm content is understood not only as an act of self-injury but also as a form of expressing feelings such as loneliness, emotional pressure, and the need for validation. Symbols like “barcode,” dark visuals, mellow music, and short texts become elements that shape meaning patterns among Gen Z. Overall, this study highlights the importance of digital literacy and attention to mental health, from society, parents, educators, to policymakers, so that the meaning of sensitive content like self-harm can be understood and addressed more wisely.